The Digital Cognitive Partner: A 4P Framework Analysis of Prospective Teacher Creativity in the Age of AI - Setyadi, Danang; Soesanto, Robert Harry; Hidayat, Dylmoon; Dosinaeng, Wilfridus Beda Nuba; Mampouw, Helti Lygia (FKIP Universitas Lampung, 2025)
Prospective teachers must be equipped with creative thinking skills to be able to design innovative mathematics learning media. However, studies on the creativity of prospective teachers are often not comprehensive and tend to focus on only one dimension of creativity. Although the 4P creativity model (Person, Process, Press, Product) provides a comprehensive analytical lens, research that integrates all four dimensions simultaneously in the context of mathematics teacher education is still rare. This study is a qualitative descriptive study that aims to describe and analyze the creativity of prospective mathematics teacher students in developing mathematics learning media. The subjects were eight students of the Mathematics Education study program who were taking the Mathematics Learning Media course and had completed a mathematics learning media development project. Data sources came from students' reflective journals when creating learning media, interview transcripts, and the learning media products that had been created. The collected data were analyzed based on Rhodes' 4P creativity framework: Person, Process, Press, and Product. The product dimension was analyzed descriptively and quantitatively using the Torrance rubric, consisting of four creativity indicators: fluency, flexibility, originality, and development. The Process dimension was analyzed based on Wallas' creative thinking framework: Preparation, Incubation, Illumination, and Verification. The person and press dimensions were then analyzed qualitatively using a thematic analysis approach. The results showed that students with high intrinsic motivation, active involvement in exploring ideas, and the ability to manage technical and time constraints tended to produce more creative and meaningful learning media. The key findings of this study significantly expand and challenge the traditional understanding of the Press dimension. The use of technology, particularly generative AI such as ChatGPT, serves not only as an external tool but also as a digital cognitive environment. AI acts as an interactive, dialogical partner, assisting in brainstorming, developing flowcharts, and solving technical problems, thereby blurring the boundaries between environmental factors (Press) and students' internal thinking processes (Process). This deep integration demonstrates that AI has become an integral part of students' cognitive workflows, implying that the 4P framework in the digital era needs to be viewed as an interconnected and flexible system, rather than as four rigidly separate pillars. Keywords: creativity, mathematics learning media, creative thinking process, case study, pre-service teachers, artificial intelligence.